Towards fully integrated Lab-on-Chip: design, assembly and experimental results. (29th June 2009) - Ghafar-Zadeh, Ebrahim; Sawan, Mohamad
We present a direct-write CMOS-based platform for Lab-on-Chip (LoC) applications. A fully automated LoC consists of several active and passive components such as biosensors and microchannels integrated on a single chip for single purpose. In this paper, we describe a low-complexity platform consisting of capacitive biosensor and microfluidic structure. The capacitive biosensor is incorporated with nonolayers of polyelectrolyte molecules for creating sensing probes where the passive components such as microchannels are implemented through a direct-write assembly technique. We demonstrate the formation of Polyelectrolyte Sensing Layer (PSL) atop a Microfabricated Gold Electrode (MGE) and CMOS sensor using Chitosan and Alginate. This is an expanded version of a paper presented at the 3rd IEEE International Workshop on Medical Measurements and Applications, 9?10 May 2008, Ottawa, ON, Canada.